A short proof of the existence of the solution to elliptic boundary problem - Ramm, Alexander G. (Global Journal of Mathematical Analysis, 2015)
There are several methods for proving the existence of the solution to the elliptic boundary problem \(Lu=f \text{in} D,\quad u|_S=0,\quad (*)\). Here L is an elliptic operator of second order, f is a given function, and uniqueness of the solution to problem (*) is assumed. The known methods for proving the existence of the solution to (*) include variational methods, integral equation methods, method of upper and lower solutions. In this paper a method based on functional analysis is proposed. This method is conceptually simple. It requires some a priori estimates and a continuation in a parameter method, which is well-known.
Keywords: Dynamical systems method (DSM); Homeomorphism; Nonlinear equations; Surjectivity